Changing patterns in chemical terrorism 1970–2021 - Castro-Delgado, Rafael; Campillo Palma, Francisco; Fernández-Arce, Lucía; Uddin, Helal; Fernández-Somoano, Ana (Frontiers in Public Health, 2025)
IntroductionChemical terrorism remains a major public health threat due to its acute and chronic effects, requiring coordinated response efforts. Although decontamination methods and training have improved, uncertainties persist, particularly as chemical agents evolve. This study examines incidents of chemical terrorism worldwide from 1970 to 2021, analyzing changes in pattern trends and typologies to earlier data, aiming to measure shifts in frequency, geographic distribution, and toxic chemical usage.MethodsData from the Global Terrorism Database (GTD) was used. Absolute frequencies and percentages were calculated to describe the distribution of the variables over time. Temporal trends were assessed using simple linear regression, reporting the coefficient of determination (r2) and p-values. Variables analyzed included incident frequency (yearly and monthly), geographic region, duration, single versus multiple attacks, success rates, suicidal intent, organizational claims, and toxin types. The number of deaths, injuries, and property damage was also analyzed. Data from 1970 to 2015 and 2016–2021 were compared to identify shifts in patterns.ResultsA total of 353 chemical terrorism cases were identified. Between 2016 and 2021, incidents declined, reversing the upward trend observed from 1970 to 2015. The most affected areas were South Asia and Middle East/North Africa. Most attacks lasted under 24 hours, involved a single incident, and had a 77.84% success rate. Nerve agents and organophosphates were among the most used (13.35%) toxins and caused the highest mortality (18.18%) and injury rates (63.33%).ConclusionChemical terrorism incidents have decreased in recent years. However, these incidents still pose risks to human life and property. Training for first responders should prioritize the detection and management of nerve agents and organophosphates. Improved detection systems and standardized protocols are imperative for strengthening response effectiveness in future incidents.